INVESTIGASI EKSPERIMENTAL MEKANISME TRANSPORTASI HYDROLYZED POLYACRYLAMIDE (HPAM) PADA MEDIA BERPORI - Gajah, Ganesha
Polymer injection is a tertiary recovery process that can ameliorate by lowering water - oil mobility ratio, because of higher polymer viscosity than formation water viscosity, which will improve oil production and recovery factor . Laboratory experiments of Hydrolyzed Polyacrylamide (HPAM) injection results appear to be in contradiction of the expected results from the theory. Polymer with 1000 ppm concentration has viscosity value 41.68 cp and 22.34 cp for ChemEOR and FP3630S, respectively, but the corresponding recovery factor is 9.49% and 15.81% of Initial Oil in Place (IOIP).That contradiction can be explained by the different values of transport mechanism parameters, i.e., Inaccessible Pore Volume (IPV) and dynamic retention (adsorption and trapping). The polymer rheology is analyzed at four different concentrations in brine water to observe the viscosity variation with shear rate at various salinities, and polymer concentrations. Investigation of polymer transport mechanisms is studied from injectivity test results of both tracer and polymer solution for the same rock characteristics. Polymer and tracer effluent concentrations are measured by UV/vis spectrophotometer (UV/vis) and Atomic Adsorption Spectrophotometer (AAS), respectively. Effluent concentration profile is used to determine the value of Inaccessible Pore Volume (IPV) and dynamic retention. Inaccessible Pore Volume (IPV) is determined at the trailing edge and dynamic retention is determined at the leading edge of Effluent concentration profile. This study also investigates the dynamic adsorption, thickness of adsorbed layer, dynamic trapping, mobility reduction or resistance factor (RF), permeability reduction or residual resistance factor (RRF), and polymer dispersivity. ChemEOR’s rheology measurement results show higher viscosity than that of FP3630S at various shear rates, salinities, and polymer concentrations. Injectivity test results show that ChemEOR has higher values of Inaccessible Pore Volume (IPV), mobility reduction, and permeability reduction than FP3630S. On the other hand, the values of dynamic retention and polymer dispersivity of ChemEOR are lower than that of FP3630S. ChemEOR and FP3630S values of Inaccessible Pore Volume (IPV) are 34% and 28%, mobility reduction or resistance factor (RF) are 4.7 and 3.6, and permeability reduction or residual resistance factor (RRF) are 4.2 and 1.8, respectively, while ChemEOR and FP3630S values of dynamic retention are 26.742 ?g/g and 38.447 ?g/g, and dispersivity are 0.038 ft2/sec and 0.039 ft2/sec. These experiment results can explaine the tendency of polymer transport mechanism. Polymer with higher Inaccessible Pore Volume (IPV) has lower dynamic retention . Polymer with higher Inaccessible Pore Volume (IPV) has higher mobility reduction or resistance factor (RF) and permeability reduction or residual resistance factor (RRF) because these three parameters relate to polymer molecular size and rock pore size. These results are supported by the dynamic trapping value that is higher for ChemEOR than FP3630S,i.e., 1.529% and 0.352%, which indicate that ChemEOR molecular size is bigger than that of FP3630S. These facts are the determining factors that cause lower recovery factor for ChemEOR injection, which essentially is explain that the polymer transport mechanisms is dominated by bigger polymer molecular size, thus not all rock pores are invaded by the polymer molecules.